Cathodic Stripping Voltammetric Determination of Dimenhydrinate - Raqi Shubietah; Ali Abu Zuhri‎‏ (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Dimenhydrinate (DMH) is a derivative of theophylline (diphenhydramine salt of 8-chloro theophylline). Both dimenhydrinate and theophylline are used as antihistamines in treatment of asthma, in addition to other important pharmaceutical uses. A three-electrode voltammetric system was used, with hanging mercury drop electrode (HMDE) as working electrode. A reduction peak of DMH at -0.2 to -0.3 V in acetate buffer, pH about 4.0 is obtained. The peak height is increased largely (tripled) in presence of Cu2+, due to the formation of DMH-Cu (I) complex. The detection limit is as low as 5x10-9 M DMH. Application of the analysis of two drugs containing dimenhydrinate was carried out, where a coefficient of variation of about 3% was obtained.